Developmental outcomes following prenatal exposure to methamphetamine: A Western Australian perspective. (3rd September 2019) - O'Connor, Angela; Seeber, Carly; Harris, Emma; Hamilton, Dale; Sachmann, Mark; Fisher, Colleen
Abstract : Aim: To describe neurodevelopmental outcomes among a cohort of Western Australian infants exposed to maternal methamphetamine use during pregnancy and to determine whether the Ages and Stages Questionnaire is a reliable screening tool for this population. Methods: Methamphetamine‐using women were approached for participation when referred to the state‐wide perinatal specialist drug and alcohol service for pregnancy care. Drug use during pregnancy was self‐reported in each trimester using a standardised questionnaire. Ages and Stages Questionnaires were completed by infant care givers at 4 and 12 months, and development was formally assessed at 12 months using the Griffiths Mental Development Scales. Griffiths results for term‐born infants in our cohort were compared to a Western Australian historical cohort of 443 healthy 1–2‐year‐olds. Results: A total of 112 methamphetamine‐using pregnant women participated in the study, who gave birth to 110 live‐born infants. Ages and Stages Questionnaires were completed for 89 (81%) and 78 (71%) of the infants at 4 and 12 months, respectively. The Ages and Stages assessment identified 30 infants (33.7%) as having a potential developmental delay at 4 months and 29 infants (38.7%) as having a potential developmental delay at 12 months. Griffiths assessments were performed on 64 (58%) of the infants, with a mean general quotient of 92.7. This was significantly lower in term‐born babies compared to the historical cohort (who had a median general quotient of 113.0). There was a weak correlation between 12‐month Ages and Stages scores and Griffiths general quotients ( r = 0.322) and no correlation between 4‐month Ages and Stages Questionnaire scores and later Griffiths results. Conclusions: Infants born to women reporting methamphetamine use during pregnancy are at increased risk of developmental delay and may warrant enhanced developmental follow‐up. However, they are a challenging group to follow due to complex psychosocial factors. Ages and Stages Questionnaires at 4 and 12 months were not helpful in screening for infants who had a developmental delay at 12 months.